2021
DOI: 10.1590/0103-8478cr20200834
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the outbreak of equine glanders in Alagoas, Brazil: Clinical, immunological, molecular, and anatomopathological findings

Abstract: Glanders is an infectious and often lethal zoonotic disease of equines caused by the bacterium, Burkholderia mallei. This condition is characterized by respiratory, lymphatic, and cutaneous lesions. In this study, we monitored the development of clinical symptoms in animals naturally infected with B. mallei across different equine breeds and also isolated and characterized the disease-causing bacteria. We studied two official glanders outbreaks in the state of Alagoas, Brazil. During the outbreaks, we performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
0
0
1
Order By: Relevance
“…O aumento relativo de casos, pode ser descrito em decorrência as aglomerações geradas por eventos equestres não fiscalizados pela defesa agropecuária, que invariavelmente reúne animais que não foram testados (Ali-Ani & Roberson, 2007;Verma, 1988). A circulação da mesma cepa da bactéria verificada em estudos realizados por Falcão, et al, (2019) e Rocha et al, (2021) na região Nordeste confirmam a relação existentes no comércio de animais interestadual e aglomerações em eventos e feira à transmissão da doença.…”
Section: Resultsunclassified
“…O aumento relativo de casos, pode ser descrito em decorrência as aglomerações geradas por eventos equestres não fiscalizados pela defesa agropecuária, que invariavelmente reúne animais que não foram testados (Ali-Ani & Roberson, 2007;Verma, 1988). A circulação da mesma cepa da bactéria verificada em estudos realizados por Falcão, et al, (2019) e Rocha et al, (2021) na região Nordeste confirmam a relação existentes no comércio de animais interestadual e aglomerações em eventos e feira à transmissão da doença.…”
Section: Resultsunclassified
“…It has a sensitivity equivalent to or greater than CF, whereas ELISA with recombinant proteins has high sensitivity and specificity (Mota & Ribeiro 2015). Rocha et al (2021) reported that a horse without clinical signs was diagnosed through indirect ELISA; later, the case started to show expectoration of mucopurulent secretion and edema of the hind limb, but even with suggestive signs of glanders and seropositivity in the indirect ELISA, the animal remained negative in the CF.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, equids that work in sugar cane fields in the forest zone of the Northeast are more frequently reported to exhibit symptomatic cases of glanders [7][8][9]. Conversely, reports on glanders in other regions generally describe asymptomatic animals or those with mild clinical changes [10,11].…”
Section: Introductionmentioning
confidence: 99%